Pengaruh Promosi Akun Instagram @Badjoelama.Co Terhadap Keputusan Pembelian Barang Preloved Pada Followers Aktif - Dhina Khoerunisa; Nur’aeni Nur’aeni; Adhie Surachman (Universitas Majalengka, 2021)
This study aims to determine the effect of the promotion of the @badjoelama.co Instagram account on purchasing decisions on active followers. This study uses a quantitative method with an associative approach. respondents in this study are active followers of @badjoelama.co. The source of the data used is from questionnaire data with active followers @badjoelama.co which is then processed using SPSS version 25. In this study, the significance correlations value is 0.000, so it can be said that there is a relationship between promotions and purchasing decisions, while the Pearson correlation value is 0.490. the level of promotion relationship with purchasing decisions is moderately correlated. The results of significant research taken from the ANOVA table, the significant value of the promotion variable (X) on the purchasing decision variable (Y) is 0.00 <0.05 and f-count 30.909 > f-table 3.09. This proves that Ho is rejected, Ha is accepted, meaning that there is a significant effect of promotion on purchasing decisions.